Subjective Well-Being of the Employee In Manufacturing Industry In Pandemic Covid-19 - Widyastuti Widyastuti; Bambang Kartono Kurniawan; Mutmainah Nur Rahma Majid (Psychosophia: Journal of Psychology, Religion, and Humanity, 2022)
This study aimed to determine the impact of the Covid-19 Pandemic on the subjective well-being of the employee in Rattan Industry Trangsan Sukoharjo, Central Java, Indonesia. The mixed methods were used in this study. There are used the well-being scale to measure the subjective well-being of the employee and also used interviews for a qualitative approach. The research subjects were 30 employees consisting of 6 women and 24 men. The subjective well-being scale used in this study refers to the concept proposed by Diener (2000) which consists of 15 items with 5 choices. The results of the t-test show that there are differences in subjective well-being between the sample of subjects and the population. The hypothetical and empirical mean t-test shows that t=58.563 (p<0.05). This study indicated that the subjective well-being of the employee in the Rattan Manufacturing Industry Trangsan is better than the population. The data from interviews show that during the pandemic, exports demand from overseas such as Australia, the USA, and Europe increased. These demands allow the employee to continue their activity and led to the salary increment of the employee. Increasing income makes workers happier at work it improves their subjective well-being. However, the employees have complained about the lack of raw materials and containers. This study is expected to provide information for the government and policymakers to facilitate the export process and procurement of raw materials. Therefore, the sustainability of the product and the production process will be able to run smoothly and it also has an impact on increasing the subjective wellbeing of the employee.